The Effectiveness of Personalisation on Health Outcomes of Older People: A Systematic Review. (February 2022) - Fatoye, Clara T.; Gebrye, Tadesse; Fatoye, Francis
Purpose: As people get older, they tend to have long-term conditions requiring health and social care intervention such as personalisation. Personalisation is person centred ensuring independence and control. To date, no systematic review has examined the effectiveness of personalisation. This review examined the effectiveness of personalisation in older people. Methods: A systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines was undertaken. Databases searched included: Science Direct and Medline (PubMed) NHSEED and CINAHL. Inclusion criteria were older people living in their own homes receiving personalisation. Excluded were studies carried out in nursing homes. Newcastle-Ottawa Scale was used for quality of assessment. Results: Search yielded 151 published studies with titles and abstracts; 143 studies were excluded and eight included. Studies included showed health outcomes of older people receiving personalisation improved significantly. Conclusions: Review found evidence of improvement in quality of life and mobility in older people.